Breech Presentation: Vaginal Versus Cesarean Delivery, Which Intervention Leads to the Best Outcomes? - Fonseca, A (2017)
INTRODUCTION: The best route of delivery for the term breech fetus is still controversial. We aim to compare maternal and neonatal outcomes between vaginal and cesarean term breech deliveries. MATERIAL AND METHODS: Multicentric retrospective cohort study of singleton term breech fetuses delivered vaginally or by elective cesarean section from January 2012 - October 2014. Primary outcomes were maternal and neonatal morbidity or mortality. RESULTS: Sixty five breech fetuses delivered vaginally were compared to 1262 delivered by elective cesarean. Nulliparous women were more common in the elective cesarean group (69.3% vs 24.6%; p < 0.0001). Gestational age at birth was significantly lower in the vaginal delivery group (38 ± 1 weeks vs 39 ± 0.8 weeks; p = 0.0029) as was birth weight (2928 ± 48.4 g vs 3168 ± 11.3 g; p < 0.0001). Apgar scores below seven on the first and fifth minutes were more likely in the vaginal delivery group (1st minute: 18.5% vs 5.9%; p = 0.0006; OR 3.6 [1.9 - 7.0]; 5th minute: 3.1% vs 0.2%; p = 0.0133; OR 20.0 [2.8 - 144.4]), as was fetal trauma (3.1% vs 0.3%: p = 0.031; OR 9.9 [1.8-55.6]). Neither group had cases of fetal acidemia. Admission to the Neonatal Intensive Care Unit, maternal postpartum hemorrhage and the incidence of other obstetric complications were similar between groups. DISCUSSION: Although vaginal breech delivery was associated with lower Apgar scores and higher incidence of fetal trauma, overall rates of such events were low. Admission to the neonatal intensive care unit and maternal outcomes were similar. CONCLUSION: Both delivery routes seem equally valid, neither posing high maternal or neonatal complications' incidence.